Institutional mechanisms for sustainable sanitation: Lessons from Japan for other Asian countries - Kazushi Hashimoto (Asian Development Bank Institute (ADBI), 2019)
Even though access to sanitation facilities has improved in the urban areas of many Asian developing countries, the pollution of public water bodies remains a serious problem. One of the causes of water pollution is improper decentralized wastewater management. This study explains the evolution of Japan's decentralized wastewater management system and extracts elements that may be useful in developing countries. These elements include the establishment of a qualification and training system for decentralized wastewater treatment facility installation businesses; the introduction of a regular desludging system; the establishment of a qualification and training system for desludging business/workers; and the establishment of a qualification and examination system for operators of PAWTPs or similar facilities mainly targeted for non-household users.
Keywords: Q25; Q53; 330; decentralized wastewater management; Japan; sanitation facilities